Imaging the interaction between dengue 2 virus and human blood platelets using atomic force and electron microscopy - Ghosh, Kanjaksha; Gangodkar, Shobha; Jain, Preksha; Shetty, Shrimati; Ramjee, Sandhya; Poddar, Pankaj; Basu, Atanu (Journal of Electron Microscopy, 2008)
Thrombocytopenia is frequently associated with dengue virus infection. Host factors such as anti-platelet immunopathogenic processes have been implicated in the origin of dengue-associated thrombocytopenia but the role of dengue virus in directly interacting with platelets and altering their hemostatic property remains incompletely understood. In the present study, we examined the effect of dengue 2 virus on the morphology and physiological activation profile of normal human platelets using atomic force microscopy, electron microscopy and flowcytometry. Platelets obtained from healthy donors were exposed to a cell culture-adapted 10(4) LD(50) dengue 2 virus isolate in vitro and the subsequent effect on morphology and activation biology studied. Our results show that dengue 2 virus exposure at doses comparable to natural viremic states in human infections can activate platelets with an increase in P-selectin expression and fibrinogen-binding property. Atomic force, scanning and transmission electron microscopy also showed typical activation-related morphological changes such as altered platelet membrane architecture, degranulation, presence of filopodia and dilatation of the open canalicular system in the dengue 2 virus-exposed platelets but not in the controls. Importantly, Japanese encephalitis virus exposure at the same dose did not activate platelets or show any morphological changes. Our findings suggest that dengue 2 virus may directly interact with and activate platelets - an event that might be important in the origin of dengue-associated thrombocytopenia. Detailed molecular characterization of this effect might provide key knowledge toward better prophylaxis of the hemostatic complications of dengue disease.
Keywords: AFM; dengue virus; Electron microscopy; platelet

In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

Investigations of magnetic and dielectric properties of cupric oxide nanoparticles - Bhalerao-Panajkar, Rohini S.; Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, S. K. (Solid State Communications, 2011)
Cupric oxide nanoparticles of similar to 8-10 nm width and 40-45 nm length self assembled as large particles similar to 1-1 5 mu m have been investigated in the 10-325 K temperature range using magnetic and dielectric measurements In magnetic measurements a single broad peak at similar to 230 K in a zero field cooled sample has been observed Coercivity in magnetization measurements at 10 K suggests that the nanoparticles are core-shell type particles with an antiferromagnetic core and a ferromagnetic shell Dielectric measurements at various frequencies from 3 7 Hz to 949 kHz exhibit a sharp peak at 284 K followed by weak anomalies around 213 and 230 K (C) 2010 Elsevier Ltd All rights reserved
Keywords: CuO nanoparticles; Dielectric; Ferroelectric transition; Ferromagnetic

In situ synthesis and surface functionalization of gold nanoparticles with curcumin and their antioxidant properties: an experimental and density functional theory investigation - Singh, Dheeraj K.; Jagannathan, Ramya; Khandelwal, Puneet; Abraham, Priya Mary; Poddar, Pankaj (Nanoscale, 2013)
Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is an active component of turmeric; it is responsible for its characteristic yellow color and therapeutic potential, but its poor bioavailability remains a major challenge. In order to improve the bioavailability of curcumin, various approaches have been used. One of the possible approaches to increase the bioavailability of curcumin is its conjugation on the surface of metal nanoparticles. Therefore, in the present study, we report the binding of curcumin on the surface of gold nanoparticles (AuNPs). The AuNPs were synthesized by the direct reduction of HAuCl4 using curcumin in the aqueous phase, without the use of any other reducing agents. We found that curcumin acts both as a reducing and capping agent, stabilizing the gold sol for many months. Moreover, these curcumin-capped AuNPs also show good antioxidant activity which was confirmed by the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical test. Thus, the surface functionalization of AuNPs with curcumin may pave a new way of using the curcuminoids towards possible drug delivery and therapeutics. Apart from the experimental study, a detailed quantum chemical calculation using density functional theory (DFT) has been performed, in order to investigate the formation of a complex of curcumin with Au3+ ions in different possible conformational isomeric forms. Our theoretical calculations indicate the evidence of electron transfer from curcumin into the Au center and essentially indicate that as a consequence of complexation, Au3+ ions are reduced to Au-0. Our theoretical results also propose that it is the breakage of intramolecular H-bonding that probably leads to the increased availability of curcumin in the presence of gold ions and water molecules.

Interchain relay of antiferromagnetic ordering in 1D Co(II) coordination polymers via pi-pi interactions - Ahmad, Musheer; Das, Raja; Mrozinski, Jerzy; Bienko, Alina; Poddar, Pankaj; Bharadwaj, Parimal K. (CrystEngComm, 2014)

Ionic control on the morphology of ytterbium manganese oxide nanorods and nanoplates in a surfactant-free synthesis and their magnetic properties - Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Here, we report the synthesis of multiferroic, single-crystalline ID YbMnO3 in nanoregime. By using ionic chemistry without the use of surfactant or template, we demonstrate control synthesis of one- and two-dimensional nanoparticles of YbMnO3. Magnetic properties of YbMnO3 show influence of morphology. Detailed alternating current (ac) and direct current (dc) magnetic study shows ferromagnetic interaction of Mn3+ and Yb3+ moments in nanorods of YbMnO3 below similar to 35 K.

Immobilization of multivalent glycoprobes on gold surfaces for sensing proteins and macrophages - Gade, Madhuri; Khandelwal, Puneet; Sangabathuni, Sivakoti; Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Poddar, Pankaj; Kikkeri, Raghavendra (Analyst, 2016)
The multivalent display of carbohydrates on the cell surface provides cooperative binding to improve the specific biological events. In addition to multivalency, the spatial arrangement and orientation of sugars with respect to external stimuli also trigger carbohydrate-protein interactions. Herein, we report a non-covalent host-guest strategy to immobilize heptavalent glyco-beta-cyclodextrin on gold-coated glass slides to study multivalent carbohydrate-protein interactions. We have found that the localization of sugar entities on surfaces using beta-cyclodextrin (beta-CD) chemistry increased the avidity of carbohydrate-protein and carbohydrate-macrophage interactions compared to monovalent-beta-CD sugar coated surfaces. This platform is expected to be a promising tool to amplify the avidity of sugar-mediated interactions on surfaces and contribute to the development of next generation bio-medical products.

Investigating the ferrimagnetic behaviour of trigonal 3C Fe7S8 nanoparticles - Jyotsna, Shubhra; Poddar, Pankaj (Bulletin of Materials Science, 2023)
The magnetic properties of trigonal 3C Fe7S8 nanoparticles, synthesized via the thermal decomposition method, are investigated using temperature-dependent zero-field cooled (ZFC) and field-cooled (FC) magnetization (M-T) curves. The M-T data, recorded at 100 and 1000 Oe, reveal magnetic ordering with high Curie transition temperature (T-C > 300 K) in the specimen. The magnetization vs. applied magnetic field (M-H) data measured in the temperature range from 7 to 300 K show that the compound exhibits ferrimagnetic ordering. The values of coercivity (H-C), saturation magnetization (M-60 kOe) and remanent magnetization (M-R) appear to increase at lower measuring temperatures. As the result of increasing M-60 kOe at lower measuring temperatures, within the temperature range of 7 to 300 K, the maximum energy product (BHmax) has the highest value of 128 kG Oe at 7 K.
Keywords: anisotropy; energy product; Fe7S8; ferrimagnetism; Pyrrhotites; trigonal phase

In situ synthesis of metal (Bi0)-semiconductor [BiOX (X = Cl, Br, and I)] nanocomposites as a highly effective catalyst for the reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (New Journal of Chemistry, 2024)
The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) has been efficiently catalyzed by in situ generated Bi-0-BiOX (X = Cl, Br, I) nanocomposites in the presence of sodium borohydride (NaBH4). The hierarchical 3D arrays of precursors (BiOCl, BiOBr, and BiOI) have been synthesized by a facile co-precipitation method at ambient temperature. The metallic Bi-0 is generated in situ by partial reduction of the Bi3+ ions in BiOX (X = Cl, Br, and I) mediated by NaBH4 during the conversion of 4-NP to 4-AP. In situ generated Bi-0-BiOX shows better catalytic activity than Bi-0-BiOX composite formed by mixing individually synthesized metallic Bi-0 particles with semiconducting BiOX nanoparticles. The Bi-0-BiOI nanocomposite demonstrated higher catalytic activity (k(app) = 0.529 min(-1)) compared to Bi-0-BiOCl (k(app) = 0.095 min(-1)) and Bi-0-BiOBr (k(app) = 0.098 min(-1)) due to its efficient conversion into metallic Bi-0. The approximate percentage composition of in situ generated metallic Bi-0 on the surface of BiOCl, BiOBr, and BiOI is nearly 10, 17, and 25%, respectively. Further, the reduction of 4-NP has been completed within 24, 22, and 6 minutes by in situ generated Bi-0-BiOCl, Bi-0-BiOBr, and Bi-0-BiOI nanocomposites from BiOCl, BiOBr, and BiOI, respectively. Extensive studies have been conducted to generate a better understanding of the actual catalytic sites present on the surface of the catalysts.

An in-depth study of the Fe-Se system at the nanoscale reveals remarkable results on the electrocatalytic oxygen evolution reaction - Singh, Dinesh; Ghalawat, Monika; Poddar, Pankaj (European Journal of Inorganic Chemistry, 2025)
A catalyst for an electrocatalytic oxygen evolution reaction (OER) is a key component of the large-scale storage of renewable energy through the conversion of water into oxygen and hydrogen. Iron-based selenide materials are currently being considered as potential options for electrocatalytic oxygen evolution reaction (OER) because of their, widespread availability, low cost, and outstanding performance. In this study, we employed a thermal decomposition method to synthesize all stable phases of the Fe-Se system, including Fe7Se8, Fe3Se4, FeSe2, and FeSe. Additionally, we slurry-coated these phases onto a three-dimensional (3D) nickel foam substrate. The prepared 3D electrodes of Fe7Se8, Fe3Se4, FeSe2, and FeSe exhibit remarkably low overpotentials of 270, 276, 299, and 289 mV at a current density of 50 mA/cm2 for OER. In addition, the catalytic activity for OER is also tested on glassy carbon electrodes to compare its performance with the Ni-foam 3D substrate. The Fe7Se8 phase in the Fe-Se system exhibits the highest catalytic activity towards OER on both substrates due to variations in the Fe2+/Fe3+ ratio and the presence of Fe vacancies (cation vacancies) within the crystal lattice. Moreover, a faradaic efficiency of 98 % was exhibited by Fe7Se8 for the oxygen evolution reaction (OER).
Keywords: Iron selenide system; OER electrocatalyst; Thermal decomposition method